Andrographolide suppresses thymic stromal lymphopoietin in phorbol myristate acetate/calcium ionophore A23187-activated mast cells and 2,4-dinitrofluorobenzene-induced atopic dermatitis-like mice model - Li CX; Li HG; Zhang H; Cheng RH; Li M; Liang JY; Gu Y; Ling B; Yao ZR; Yu H (Dove Medical Press, 2016)
Chun-xiao Li,* Hua-guo Li,* Hui Zhang,* Ru-hong Cheng, Ming Li, Jian-ying Liang, Yan Gu, Bo Ling, Zhi-rong Yao, Hong Yu Department of Dermatology, Xinhua Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China *These authors contributed equally to this work Background: Atopic dermatitis (AD) is one of the most common inflammatory cutaneous diseases. Thymic stromal lymphopoietin (TSLP) has been demonstrated to be an important immunologic factor in the pathogenesis of AD. The production of TSLP can be induced by a high level of intracellular calcium concentration and activation of the receptor-interacting protein 2/caspase-1/NF-κB pathway. Andrographolide (ANDRO), a natural bicyclic diterpenoid lactone, has been found to exert anti-inflammatory effects in gastrointestinal inflammatory disorders through suppressing the NF-κB pathway. Objective: To explore the effect of ANDRO on the production of TSLP in human mast cells and AD mice model. Methods: We utilized enzyme-linked immunosorbent assay, real-time reverse transcription polymerase chain reaction analysis, Western blot analysis, and immunofluorescence staining assay to investigate the effects of ANDRO on AD. Results: ANDRO ameliorated the increase in the intracellular calcium, protein, and messenger RNA levels of TSLP induced by phorbol myristate acetate/calcium ionophore A23187, through the blocking of the receptor-interacting protein 2/caspase-1/NF-κB pathway in human mast cell line 1 cells. ANDRO, via oral or local administration, also attenuated clinical symptoms in 2,4-dinitrofluorobenzene-induced AD mice model and suppressed the levels of TSLP in lesional skin. Conclusion: Taken together, ANDRO may be a potential therapeutic agent for AD through suppressing the expression of TSLP. Keywords: atopic dermatitis, thymic stromal lymphopoietin, andrographolide, human mast cell